Basement membrane zone IgE deposition is associated with bullous pemphigoid disease severity and treatment results. (1st May 2020) - Kamata, A.; Kurihara, Y.; Funakoshi, T.; Takahashi, H.; Kuroda, K.; Hachiya, T.; Amagai, M.; Yamagami, J.
Summary: Background: A subset of patients with bullous pemphigoid (BP) show deposition of IgE in the basement membrane zone (BMZ), yet the relationship between BMZ IgE and the clinical presentation of BP remains unclear. Objectives: To investigate the relationship between IgE deposition, IgE levels in serum, and disease severity in patients with BP. Methods: We investigated IgE autoantibodies in 53 patients with BP by direct immunofluorescence (DIF), indirect immunofluorescence and enzyme‐linked immunosorbent assay. Results: Of 53 patients with BP, 23 (43%) had IgE deposition, 10 (19%) of whom were IgE+ and 13 (25%) IgE± according to DIF analyses. Erosion/blister (E/B) Bullous Pemphigoid Disease Area Index (BPDAI) scores were significantly higher in IgE+ patients than in IgE− patients ( n = 15), while no significant differences were found for urticaria/erythema BPDAI scores. IgE+ and IgE± patients took longer to reduce their E/B BPDAI score by 75% after systemic corticosteroid treatment. BP180‐IgE levels were significantly higher among IgE+ patients than IgE± or IgE− patients ( n = 10). Total IgE levels in the serum and blood eosinophil counts did not differ between IgE+, IgE± and IgE− patients. A significant correlation was detected between BP180‐IgG and BP180‐IgE, but not between BPDAI scores and any of BP180‐IgG, BP180‐IgE or blood eosinophil count. Conclusions: IgE deposition in the BMZ is associated with higher E/B BPDAI scores and longer treatment periods. We conclude that IgE binding in the BMZ may contribute to BP pathogenesis by promoting blister formation. What's already known about this topic? BP180‐IgE autoantibodies have an important role in the pathogenesis of bullous pemphigoid (BP). A subset of patients with BP display deposition of IgE within the basement membrane zone (BMZ) of skin tissue. What does this study add? Patients with in vivo IgE deposition in the BMZ displayed higher erosion/blister Bullous Pemphigoid Disease Area Index (BPDAI) scores, while urticaria/erythema BPDAI scores were not significantly different. Patients with in vivo IgE deposition in the BMZ took longer to reduce their erosion/blister BPDAI score by 75% after systemic corticosteroid treatment. BP180‐specific IgE levels in serum were higher among patients with linear IgE deposition in the BMZ than in those with granular or no IgE deposition.